2017
DOI: 10.1080/17448689.2017.1399596
|View full text |Cite
|
Sign up to set email alerts
|

A Broad Alliance of Civil Society Organizations on Climate Change Mitigation: Political Strength or Legitimizing Support?

Abstract: One hundred and one very different organizations joined together prior to the election for the Norwegian parliament in 2013 in order to make climate change mitigation the most important issue in the election campaign. The alliance (CE2013) agreed on six political demands relating to mitigation. In this article, we categorize the 101 organizations and discuss their identity and objectives according to these demands. The analysis demonstrates that even though a broad variety of organizations joined the campaign,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In addition, though many governments view CSOs as legitimate and helpful partners, the situation may differ from place to place. Thus, in countries where CSO activities are suppressed, civic groups ought to adapt different approaches in responding to diverse situations and government policies and positions on particular issues (Pollard & Court, 2005;Nilsen, Strømsnes, & Schmidt, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, though many governments view CSOs as legitimate and helpful partners, the situation may differ from place to place. Thus, in countries where CSO activities are suppressed, civic groups ought to adapt different approaches in responding to diverse situations and government policies and positions on particular issues (Pollard & Court, 2005;Nilsen, Strømsnes, & Schmidt, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Nilsen, Strømsnes and Schmidt (2018) analyzes the efforts of 101 different organizations that came together under the umbrella of climate change mitigation just before the 2013 Norwegian parliamentary elections. The aim of the group was 'to make climate change mitigation the most important issue in the election campaign' (p. 20).…”
Section: Csos In Europe: a Call To Duty Or An Europeanization Agenda?mentioning
confidence: 99%
“…Work in this cluster of 18 (22%) articles addresses voluntary organizations in local environmental politics (e.g., Daneri et al, 2021), environmental justice movements (Vandepitte et al, 2019), advocacy and litigation coalitions (Aamodt, 2018; Holm & Berardo, 2020; Nilsen et al, 2018), the role of religious and indigenous organizations in environmental conservation teaching and awareness (e.g., Brown et al, 2021; Ellingson et al, 2012; Mlaki & Massawe, 2019; Standley et al, 2009), nonprofit scientific institutions as brokers of credible climate change information (e.g., Wagner et al, 2021), and the role of voluntary organizations in participatory governance or as democracy-building, bottom-up actors in climate action (e.g., Greenspan et al, 2022; Van Veelen & Eadson, 2019). Two articles address advocacy organizations vis-à-vis the commercial sector (e.g., Odziemkowska, 2022; Spitz et al, 2021).…”
Section: Who’s (Not) Talking About Climate Change? a Review Of Past S...mentioning
confidence: 99%
“…A study investigating civic engagement to advance climate change mitigation in Norway described how 101 diverse organisations pushed for that agenda to be key in the election campaign resulting in the agreement to adopt demands related to climate improvement (Nilsen, Strømsnes & Schmidt, 2018). Similarly, a study documenting civic engagement for environment conservation in Canada reported that forming a coalition of diverse organisations enabled them to be more effective to pursue the cause to influence the government (Burton, 2019).…”
Section: Social Mediamentioning
confidence: 99%